APLICAÇÃO DO MÉTODO PROBIT PARA A CALIBRAÇÃO DE ÍNDICES TÉRMICOS PARA ESPAÇOS ABERTOS - Kruger, Eduardo; Souza, Henor; Cristeli, Pablyne; Costa, Tamiris; Rossi, Francine (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
In climate-responsive urban planning, it is necessary to adapt existing thermal index to specific local conditions, a process commonly called calibration. In this article, two distinct indices are calibrated for Curitiba, PR, based on empirical data: the Universal Thermal Climate Index (UTCI) and the Physiological Equivalent Temperature (PET) index. The objective was to present the calibration of both indices for Curitiba, PR, a high-altitude location with temperate climate (Cfb). Climatic and subjective data were obtained in outdoor thermal campaigns with concurrent questionnaire surveys between 2009 and 2010, covering summer, autumn and winter. For the calibration, the Probit method was employed. Results showed larger discrepancies for the lower limit of the comfort range in both indices, which may reflect the longer exposure to cold situations in Curitiba, not just outdoors but also indoors, when compared to the European life style where both indices originate.